PELAKSANAAN PERATURAN PEMERINTAH NOMOR 18 TAHUN 2016 DI RSUD KARAWANG - Siti Nursanti; Yanti Tayo; Wahyu Utamidewi (Universitas Lambung Mangkurat, 2019)
Government regulations related to regional apparatus number 18 of 2016 changed the status of regional public hospitals from regional technical institutions to limited regional service units under the Karawang District Health Office. Decentralization of the health sector entered a new era, Government Regulation number 18 of 2016 made the Health Service the only government agency that deals with the health sector from starting to Promotive, preventive, curative and rehabilitative efforts. The purpose of this study was to determine the communication activities of the Karawang District Health Office in the application of Government Regulation number 18 of 2016. This study used a qualitative research method with a case study approach. Karawang Regency, and Chairperson of the Karawang Regency Hospital Supervisory Board. The results of this study are internal communication from the top down or the bottom up is easier to do both directly, and indirectly, direct communication is done by superiors by telephone and then followed up using official letters.